Crucial breakthrough of second near-infrared biological window fluorophores: design and synthesis toward multimodal imaging and theranostics. (4th May 2018) - He, Shuqing; Song, Jun; Qu, Junle; Cheng, Zhen
Abstract : Recent advances in the chemical design and synthesis of fluorophores in the second near-infrared biological window (NIR-II) for multimodal imaging and theranostics are summarized and highlighted in this review article. Abstract : The development of fluorophores and molecular probes for the second near-infrared biological window (NIR-II, 1000–1700 nm) represents an important, newly emerging and dynamic field in molecular imaging, chemical biology and materials chemistry. Because of reduced scattering, minimal absorption and negligible autofluorescence, NIR-II imaging provides high resolution, a high signal-to-noise ratio, and deep tissue penetration capability. Among various state-of-the-art bioimaging modalities, one of the greatest challenges in developing novel probes is to achieve both high resolution and sensitivity. The chemical design and synthesis of NIR-II fluorophores suitable for multimodal imaging is thus emerging as a new and powerful strategy for obtaining high-definition images. NIR-II fluorophores may convert NIR-II photons into heat for photothermal therapy and be excited by NIR-II light to produce singlet oxygen for photodynamic therapy. The presence of simultaneous diagnostic and therapeutic capabilities in a single probe can be used for precise treatment. In this review, we have focused on recent advances in the chemical design and synthesis of NIR-II fluorophores from small organic molecules to organic and inorganic nanoparticles, and we have further discussed recent advances and key operational differences in reported NIR-II imaging systems and biomedical applications based on NIR-II imaging, such as multimodal imaging, photothermal and photodynamic therapy, guidance for intraoperative surgery, and drug delivery.